Rancang Bangun Sistem Informasi Katalog Produk BULOG berbasis Website menggunakan Framework Codeigniter - Budi Santoso; Diah Priharsari; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In the process of daily activities at Perum Bulog, the Malang branch office still uses the conventional method, namely, marketing to consumers using paper leaflets that are distributed or given directly to consumers by the BULOG commercial division. And consumers who want to join as RPK (official BULOG distributor) must come and register directly at the Malang branch of BULOG. To overcome this, an online information system is needed in order to organize marketing management properly. Utilization of internet technology in the marketing efforts of a company's products is one solution in increasing sales and income in the business world. To overcome the barriers of space and time that have been obstacles to conventional sales systems, this cannot be separated from the role of the web as a source of information on the internet. The implementation of the development of the BULOG Product Catalog Information System uses one of the SDLC (System Development Life Cycle) methods, namely the Waterfall Model. The Waterfall model was chosen by the author over other models because the author feels that this model is the most effective and suitable model to help solve this problem. Development using the Waterfall model is carried out in stages and a detailed definition of each phase is carried out, especially in the system requirements planning phase at the beginning of the application process. Furthermore, in this development the author uses the CodeIgniter Framework, because the CodeIgniter framework is relatively easy to understand and CodeIgniter also provides various kinds of libraries that can facilitate application development.